Incidence of anthropometric variables on the performance of top Optimist sailors - Palomino-Martin, A.; Quintana-Santana, D.; Quiroga-Escudero, M. E.; González-Muñoz, A. (Journal of Human Sport & Exercise, 2017)
The aim of this study was to determine the anthropometric profile of top Optimist sailors to examine how anthropometric variables influence their performance, taking the wind conditions into account. The study comprised 180 sailors (158 males and 22 females) aged 11-15 years competing in the Optimist World Sailing Championship held in Las Palmas de Gran Canaria, Spain, from 23 July to 3 August 2003. A descriptive correlational design was used. Assessments were made before and during the championship. The variables studied were body weight, height, arm span, lengths, fat tissue, muscle tissue, somatotype and performance level, in relation to race finishing place. The mean characteristics presented by the Top Group (sailors ranked 1 to 45) were: body weight (48.3 ± 6.4 kg), height (159.9 ± 5.4 cm), arm span (167.4 ± 6.5 cm), trunk length (37.2 ± 3 cm), lower limb length (90.7 ± 3.9 cm), fat tissue (10.5 ± 1.6%), muscle tissue (45.5 ± 2.1%) and somatotype (endomorphy 2.4 ± 0.9; mesomorphy 4 ± 2.5 and ectomorphy 3.3 ± 0.9). A close relation was observed between finishing place and the variables of weight, height, age, arm span, lower limb length, upper arm girth, sum of skinfolds, muscle weight, bone weight and residual weight. Top sailors tend to be meso-ectomorphic, with significant values for muscle mass and linearity and low fat content.